Sengketa Dokdo/Takeshima: Kedaulatan, Kontrol De Facto, dan Penyelesaian Hukum Internasional (Unclos & San Francisco, 2025) - Helen Tina BR Lumban Batu; Padrisan Jamba (CV Rewang Rencang, 2025)
Dokdo/Takeshima Island remains a source of tension between South Korea and Japan. This study collects and examines international legal documents, historical maps, and diplomatic archives as primary sources. In addition, a number of relevant court decisions and state practices are compared to determine the direction of jurisprudence. Japan adheres to its interpretation of history and the dynamics of the region after World War II, while South Korea emphasizes geographical proximity, historical evidence, and the fact that it has long managed and stationed officials on the island. When viewed from the principle of effective [1]control, South Korea's claim appears more convincing, even though the country refuses to bring this issue to the International Court of Justice because it does not consider it a dispute. The findings of the study confirm the need for peaceful resolution channels such as mediation and arbitration to maintain regional stability, especially with the strengthening of geopolitical tensions and maritime security issues until 2025.